Partial tibial nerve transfer for foot drop from deep peroneal palsy: Lessons from three pediatric cases. Issue 1 (22nd September 2020) - Crowe, Christopher S.; Mosca, Vincent S.; Osorio, Marisa B.; Lewis, Sarah P.; Tse, Raymond W.
Abstract: Peroneal nerve palsy with resultant foot drop has significant impacts on gait and quality of life. Traditional management includes ankle‐foot‐orthosis, tendon transfer, and arthrodesis—each with certain disadvantages. While nerve transfers for peroneal nerve injury have been reported in adults, with variable results, they have not been described in the pediatric population. We report the use of partial tibial nerve transfer for foot drop from deep peroneal nerve palsy in three pediatric patients. The first sustained a partial common peroneal nerve laceration and underwent transfer of a single tibial nerve branch to deep peroneal nerve 7 months after injury. Robust extensor hallucis longus and extensor digitorum longus reinnervation was obtained without satisfactory tibialis anterior function. The next patient sustained a thigh laceration with partial sciatic nerve injury and underwent transfer of two tibial nerve branches directly to the tibialis anterior component of deep peroneal nerve 9 months after injury. The final patient sustained a blast injury to the posterior knee and similarly underwent a double fascicular transfer directly to tibialis anterior 4 months after injury. The latter two patients obtained sufficient strength (MRC 4–5) at 1 year to discontinue orthosis. In all patients, we used flexor hallucis longus and/or flexor digitorum longus branches as donors without postoperative loss of toe flexion. Overall, our experience suggests that early double fascicular transfer to an isolated tibialis anterior target, combined with decompression, could produce robust innervation. Further study and collaboration are needed to devise new ways to treat lower extremity nerve palsies.